2020
DOI: 10.1177/2045125320980573
|View full text |Cite
|
Sign up to set email alerts
|

Protracted withdrawal syndrome after stopping antidepressants: a descriptive quantitative analysis of consumer narratives from a large internet forum

Abstract: Background: Protracted withdrawal syndrome (PWS) after stopping antidepressants (frequently also referred to as post-acute withdrawal syndrome or PAWS) has been described in a few case reports. However, a detailed quantitative analysis of specific symptom manifestations in antidepressant PWS is still lacking. Methods: We extracted patient narratives from a large English-language internet forum SurvivingAntidepressants.org , a peer support site concerned about withdrawal from antidepressants. PWS was ascertaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 70 publications
0
47
0
2
Order By: Relevance
“…[2][3] In addition, without careful management, protracted withdrawal can result in extended periods of suffering over many months and even years, and symptoms that are often untreatable. 4 Recent research concluded that over half of people coming off ADs will suffer withdrawal symptoms, of which one in two cases will be severe. 5 This suggests that AD withdrawal is likely to be something that GPs frequently see in their practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3] In addition, without careful management, protracted withdrawal can result in extended periods of suffering over many months and even years, and symptoms that are often untreatable. 4 Recent research concluded that over half of people coming off ADs will suffer withdrawal symptoms, of which one in two cases will be severe. 5 This suggests that AD withdrawal is likely to be something that GPs frequently see in their practice.…”
mentioning
confidence: 99%
“…However, when healthcare services fail to recognise these symptoms or misdiagnose them as a recurrence of previous distress, functional neurological (FND), or even medicinally unexplained (MUS) symptoms, 2-3 many patients seek support elsewhere. Most commonly this support is provided by online withdrawal support communities on dedicated websites 4 and, now increasingly commonly, in private Facebook groups. 6 My recent publication 'The role of Facebook groups in the management and raising of awareness of antidepressant withdrawal: is social media filling the void left by health services?'…”
mentioning
confidence: 99%
“…Indeed, the whole concept of ‘regular tapering’ does not appear to exist as the current practice is that patients and doctors are improvising in a variety of patient- and doctor-specific ways to facilitate the tapering of medication in patients experiencing significant withdrawal. 3 It may also prove difficult, for example, in the case of venlafaxine for which small doses do not exist, to randomise patients to a ‘regular tapering’ arm, given widespread access to venlafaxine tapering strips for a personal and flexible tapering trajectory.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Post-acute withdrawal or protracted withdrawal syndromes from antidepressants can be severe and long-lasting, and its manifestations clinically heterogeneous. 3 Given high rates of long-term prescribing, particularly in deprived areas, 4 withdrawal and inability to discontinue antidepressant medication represent a significant public health problem, 5 particularly given persisting doubts about real-world effectiveness 6 and indications that continued drug treatment with antidepressant medications may stimulate processes that run counter to the initial acute withdrawal effects of a drug (the oppositional model of tolerance). 7 Patient surveys suggest current inadequacy of healthcare systems to recognise and manage prescribed drug withdrawal with tapering medication, and patient feedback, 5 , 8 , 9 which is matched by research showing that only a small minority of general practitioners feel sufficiently knowledgeable about withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…20 Although withdrawal symptoms are traditionally thought to be short-lived, accumulating evidence suggests they can sometimes be protracted over many weeks or months. [21][22][23] In addition to this, withdrawal may itself precipitate relapse of some conditions, including schizophrenia or psychosis and bipolar disorder, elevating the risk of relapse for several months. 19 24 25 Studies of lithium treatment in people diagnosed with bipolar disorder, for example, show that the risk of developing an episode following the discontinuation of lithium is higher than it was prior to lithium being started.…”
Section: Withdrawal Effects In Psychiatric Trialsmentioning
confidence: 99%